Variability, sustainability and productivity of banana and lemongrass intercropping based on yield components and competitive indices - de Jesus, Paulo Ricardo Rodrigues [UNESP]; Leonel, Sarita [UNESP]; Leonel, Magali [UNESP]; Cândido, Hebert Teixeira [UNESP]; Tecchio, Marco Antonio [UNESP] (Elsevier, 2025)
The diversification of banana germplasm is necessary for a sustainable and profitable crop. Intercropping can be a promising technique for more efficient and sustainable horticultural crops production. One of the biggest challenges of intercropping with two or more crops is maintaining the productivity of each single crop. This study was performed in the Midwest of the state of São Paulo, in the subtropical region of southeastern Brazil to evaluate the yield performance and competitiveness indices of four banana (‘BRS FHIA Maravilha’, ‘BRS Pacoua’, ‘SCS451 Catarina’ and ‘Prata Anã’) genotypes in intercropping with lemongrass. Field experiments were conducted over two consecutive seasons. Cropping systems has no effect on banana yields, but variations were observed between cultivars. The highest yields were obtained in the bananas ‘SCS451 Prata Catarina’ and ‘BRS FHIA Maravilha’ at both harvest seasons, while the ‘BRS Pacoua’ showed the lowest yields. Lemongrass intercropped with banana cultivars showed no difference in yield in the two years of cropping. However, the average cumulative yield of lemongrass increased according to the harvest time evaluated, with 10.9 t ha-1 in the first year and 24.5 t ha-1 in the second year. The average total land use efficiency and the area-time equivalent ratio had values > 1.0, indicating higher yields in intercropping compared to sole cropping. The competitive relationship between the two crops showed that the banana cultivars were less competitive for environmental resources than lemongrass.
Keywords: Banana cultivars; Crop management; Cymbopogon citratus; Medicinal crop; Musa sp